Refutation Texts in the Last Decade: A Bibliometric Exploration of Trends and Insights - Nur Endah Susilowati; Nuzulira Janeusse Fratiwi; Mohd Zaidi Bin Amiruddin; Nur Habib Muhammad Iqbal (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2025)
This study aims to explore research and publication trends related to refutation texts over the past ten years using bibliometric analysis. Data was obtained from the Scopus database of 115 documents published in 2015-2024 for “refutation texts” or “refutational texts” or “rebuttal texts”. The data obtained showed fluctuations in the number of publications, with the highest peak occurring in 2022. The main authors in this field include Kendeou, Sinatra, and Danielson, with the largest contributions coming from the United States, followed by European countries such as Germany and Canada. The dominant research subjects are social sciences and psychology, with a focus on the use of refutation texts to create cognitive conflict and change students’ conceptions. Keyword co-occurrence analysis shows a close relationship between refutation texts, misconceptions, and conceptual change. These findings highlight the importance of a refutation text-based approach in overcoming students’ misconceptions, as well as opening up opportunities for further research on its application in technology-based learning and student motivation.